Combining Dipole and Loop Coil Elements for 7 T Magnetic Resonance Studies of the Human Calf Muscle - Cap, Veronika; Rocha Dos Santos, Vasco Rafael; Repnin, Kostiantyn; Červený, David; Laistler, Elmar; Meyerspeer, Martin; Frass-Kriegl, Roberta (Sensors (Basel, Switzerland), 2024)
Combining proton and phosphorus magnetic resonance spectroscopy offers a unique opportunity to study the oxidative and glycolytic components of metabolism in working muscle. This paper presents a 7 T proton calf coil design that combines dipole and loop elements to achieve the high performance necessary for detecting metabolites with low abundance and restricted visibility, specifically lactate, while including the option of adding a phosphorus array. We investigated the transmit, receive, and parallel imaging performance of three transceiver dipoles with six pair-wise overlap-decoupled standard or twisted pair receive-only coils. With a higher SNR and more efficient transmission decoupling, standard loops outperformed twisted pair coils. The dipoles with standard loops provided a four-fold-higher image SNR than a multinuclear reference coil comprising two proton channels and 32% more than a commercially available 28-channel proton knee coil. The setup enabled up to three-fold acceleration in the right-left direction, with acceptable g-factors and no visible aliasing artefacts. Spectroscopic phantom measurements revealed a higher spectral SNR for lactate with the developed setup than with either reference coil and fewer restrictions in voxel placement due to improved transmit homogeneity. This paper presents a new use case for dipoles and highlights their advantages for the integration in multinuclear calf coils.
Keywords: kosterní svaly; Magnetic Resonance Imaging; muscle metabolism; magnetic resonance imaging; poměr signál - šum; Lactic Acid; fantomy radiodiagnostické; kyselina mléčná; magnetic resonance spectroscopy; lidé; magnetická rezonanční tomografie; Muscle, Skeletal; magnetická rezonanční spektroskopie; Phantoms, Imaging; ultra-high field; Signal-To-Noise Ratio; radiofrequency coil; Magnetic Resonance Spectroscopy; Humans